Flexible power point tracking aided power ramp rate control for photovoltaic systems with small energy storage capacity - Yan, Hein Wai (2023)
Solar photovoltaic (PV) power generation inherently fluctuates due to erratic weather conditions. Although an energy storage system (ESS) can effectively mitigate these fluctuations, conventional methods require a large ESS capacity to control both increasing and decreasing rates of PV power change. This article explores an opportunity to reduce the required ESS capacity in PV power smoothing applications by delegating the power smoothing during positive irradiance transients to a flexible power point tracking algorithm. Therefore, the ESS only needs to regulate the power ramp rate during negative irradiance transients and it no longer requires the reserved capacity for positive transients. After discharging the ESS, the proposed control fully restores it without violating the allowed ramp rate. The efficacy of the proposed power ramp rate control under rapid irradiance transients is demonstrated experimentally using a laboratory-scale setup. Additionally, based on simulated case studies using a specific real-field one-day irradiance profile, the proposed control allows around 64% reduction in the required ESS capacity compared to the conventional ESS-based control.